Edukasi Pemanfaatan Madu Alami untuk Mencegah Anemia pada Ibu Hamil di PMB CH Mala Kota Palembang - Deby Meitia Sandi; Tri Restu Handayani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Anemia during pregnancy remains a major public health concern in Indonesia, contributing to increased maternal and fetal morbidity. Iron supplementation often faces challenges in compliance and side effects, prompting the need for natural alternatives. Natural honey has been shown to help increase hemoglobin levels due to its iron, folate, and antioxidant content. Objective: This community service aimed to educate pregnant women on the benefits and utilization of natural honey as a complementary strategy to prevent anemia. Method: The activity was conducted at PMB CH Mala in Palembang City using health education sessions, demonstrations, and distribution of printed educational materials. Participants' knowledge and hemoglobin levels were assessed pre- and post-intervention using a questionnaire and digital hemoglobinometer. The intervention lasted for 2 weeks, with honey consumption recommended at 2 tablespoons daily. Results: There was a notable improvement in participants' knowledge about anemia and the role of honey. Preliminary observations also showed a slight increase in hemoglobin levels among pregnant women who regularly consumed honey during the intervention period. Conclusion: Educational intervention on the use of natural honey proved effective in improving knowledge and potentially supporting anemia prevention among pregnant women. Further studies are recommended to evaluate long-term outcomes and larger-scale implementation.